Inflammation, Lp(a) and cardiovascular mortality: results from the LURIC study - Wissel, Stephanie; Scharnagl, Hubert; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Moissl-Blanke, Angela P.; Krämer, Bernhard; März, Winfried (Clinical research in cardiology, 2025)
Objective Lipoprotein(a) [Lp(a)] concentrations have been associated with cardiovascular risk. Recent studies suggested an interaction between systemic inflammation assessed via high-sensitivity C-reactive protein (hsCRP) and Lp(a). This study aimed to evaluate whether Lp(a), hsCRP, and interleukin-6 (IL-6) levels are associated with cardiovascular mortality in a German hospital-based cohort. Methods Data were drawn from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study, including 3,316 patients undergoing coronary angiography. Lp(a) was measured by immunoturbidimetry and categorized into three strata (< 50 mg/dL, n = 2668; 50-100 mg/dL, n = 482; > 100 mg/dL, n = 163). HsCRP was measured by immunonephelometry and categorized by intervals (1st < 1 mg/L, 2nd 1-2 mg/L and 3rd interval > 2 mg/L). IL-6 was measured by ELISA and categorized into two groups (1st < 3.2 ng/L, 2nd ≥ 3.2 ng/L). The primary outcome was cardiovascular disease (CVD) mortality, analyzed using Cox proportional hazards models and logistic regression. Results Participants were predominantly male, with a mean age of 62.6 years. Extremely high Lp(a) (> 100 mg/dL) was associated with increased cardiovascular mortality (HR 1.5, 95% CI 1.06-2.12) compared to Lp(a) < 50 mg/dl. Both hsCRP (> 2 mg/L, HR 1.39, 95% CI 1.08-1.79 third vs. first interval) and more so IL-6 (HR 1.92, 95% CI 1.64-2.23, upper vs. lower half), were independently associated with higher CVD mortality. While hsCRP did not increase the Lp(a)-CVD mortality in stratified analysis, high IL-6 conferred an increased risk at Lp(a) levels > 100 mg/dL (HR 1.25, 95% CI 1.09-1.44). Conclusion HsCRP and IL-6 are associated with cardiovascular mortality. Markedly elevated Lp(a) is associated with an increased risk of cardiovascular mortality in the context of high systemic inflammation. Anti-inflammatory treatments may provide additional therapeutic benefits for individuals with high Lp(a). Graphical Abstract